Analisis Tindak Tutur Ilokusi Asertif dan Ilokusi Direktif Nisa Rostiana dalam Kanal Youtube Kinderflix - Audya Nilam Nariswari; Dewi Trisnawati; Elsa Revalina; Hawa Amwalya Akasyah; Nurlaili Ismiati; Asep Purwo Yudi Utomo; Rossi Galih Kesuma; Bivit Anggoro Prasetyo Nugroho (Pusat Riset dan Inovasi Nasional, 2025)
Pragmatics is a branch of semiotic linguistics. Semiotics studies verbal language, symbols, signs, and their meaning in the means of life. Pragmatics examines the relationship between language and context and the relationship between language use and its speakers. This article, is more focused on discussing the analysis of speech acts in a video, where the definition of speech acts itself is an individual symptom, psychological in nature, and its continuity is determined by the speaker's language skills in dealing with certain situations and in speech acts that are seen are the meaning or meaning of the actions in the speech. The purpose of this study is to determine the directive and assertive speech acts of Nisa Rostiana on the Kinderflix YouTube channel. The research method used is a descriptive qualitative research method and pragmatic approach. The research data results from the identification or analysis of Nisa Rostiana's directive and assertive speech acts on the Kinderflix YouTube channel. The data collection technique used is a pragmatic approach in the form of free listening techniques, note-taking techniques, and documentation techniques. The pairing technique was also used to analyze the data. The informal method is used as a data presentation technique in this research. The data presentation is poured into a table containing some assertive and directive utterances and their reasons. The result of the analysis is 94 utterances which include 47 assertive utterances and 47 directive utterances. This research produces some assertive speeches that describe characteristics, state information, and express opinions. This research also produces some directive speeches that build active involvement with invitations, giving direct orders, and giving orders through requests. This study is useful as a guideline in determining assertive and directive illocutionary speech in a video, besides that the author can pay more attention to the differences in assertive and directive illocutionary speech acts.